2010
DOI: 10.1007/s00464-009-0861-0
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative infliximab treatment and postoperative complications after laparoscopic restorative proctocolectomy with ileal pouch–anal anastomosis: a case-matched study

Abstract: The study findings showed no adverse impact from previous infliximab therapy on the laparoscopic IPAA postoperative course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 27 publications
0
33
1
2
Order By: Relevance
“…In several studies, prior biological therapy was considered to have a negative effect on the results of the surgical treatment in UC [20,21], although this is not supported by other observations [22][23][24] or the most recent case-matched study [25]. Our study indicated only four cases of an early postoperative complication among the 16 patients who had received infliximab treatment and therefore suggests that prior biological therapy is not associated with a higher rate of complications.…”
Section: Discussioncontrasting
confidence: 44%
“…In several studies, prior biological therapy was considered to have a negative effect on the results of the surgical treatment in UC [20,21], although this is not supported by other observations [22][23][24] or the most recent case-matched study [25]. Our study indicated only four cases of an early postoperative complication among the 16 patients who had received infliximab treatment and therefore suggests that prior biological therapy is not associated with a higher rate of complications.…”
Section: Discussioncontrasting
confidence: 44%
“…W innych badaniach natomiast wykazano jedynie zwiększenie ryzyka wy stąpienia powikłań infekcyjnych [80,81]. Istnieją jednak dane przeczące także i takiej zależności.…”
Section: Steroidy Stosowane Przewlekle (Powyżej 20 Mg/unclassified
“…Gender distribution was equivalent with both groups having 45% male and 55% female. The mean age in the IFX group was slightly younger with an average of 15.0 years (range 11 to 18) compared to 16.4 years (range, [8][9][10][11][12][13][14][15][16][17][18] in the control group.…”
Section: Resultsmentioning
confidence: 99%
“…Reports in the adult literature provide conflicting results of infliximab's potential to impact postoperative outcomes [3][4][5][6][7][8][9]. However, to date, there have been no studies examining the post-IPAA effects of preoperative treatment with infliximab specifically in children.…”
mentioning
confidence: 82%